Models to Estimate Amino Acid Requirements for Broiler Chickens: A Review - Waldroup , P. W.; Oviedo-Rondon, E. O. (International Journal of Poultry Science, 2002)
Computerized growth models can be a useful tool to determine more profitable and accurate concentrations and balance of dietary amino acids and other nutrients for broiler chickens. The methodology of mathematical modeling can be rapidly accepted in poultry nutrition and research due to the complexity of nutrient requirement estimations in practical and economical terms, and the necessity to have some quantitative margin of safety in the prediction of broiler performance for decision-making applications in the poultry industry. This paper reviews the current problems related to the methodologies for amino acid requirement estimation for growing chickens, the development of mathematical modeling of growth and their applications in poultry nutrition, and a short chronological review of the evolution of computer growth models.